MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM GAMES TOURNAMENT (TGT) UNTUK MENINGKATKAN AKTIVITAS DAN PRESTASI BELAJAR GEOGRAFI - Dewi Sri Wahyuningsih (JPG (Jurnal Penelitian Geografi), 2013)
The aim of this research was to find out the implementation of cooperative learning model of TGT type to improve the activity and achievement of learning geography at XI IPS 3 class of SMA Negeri 3 Metro. This research was classroom action research which was conducted in three cycles. Cooperative learning TGT type consisted of 5 stages, namely the representation of class, studying in groups, games, tournaments, and group awards. This research was conducted at SMA Negeri 3 with Metro whose subject were 34 students consisting of 20 men and 14 women, the researcher, and geography teacher. The data taken were in the form of test, questionnaire, and observation.                                                   The result of the research showed that by implementing cooperative learning model of TGT with puzzles and Scrabble, the average students’ activity of learning geography which was suitable with the aspect observed in cycle I was 59% and in cycle II improved 13.7% so it became 72.7%, and again improved in cycle III 12.6% so it became 85.3%. While the percentage of students’ comprehensive in learning geography based on applying academic tournaments in cycle I was 57.6% and it improved 4.5% so it became 62.1% and again improved in cycle III 29.1% so it became 91.2% Concerning the results of this research, the conclusion was by implementing cooperative learning model of TGT type, it can improve the activity and achievement of learning geography at XI IPS 3 class of SMA Negeri 3 Metro. Keywords: Cooperative TGT, Activity, Achievement